Patients Undergoing Subacute Physical Rehabilitation following an Acute Hospital Admission Demonstrated Improvement in Cognitive Functional Task Independence - Steven M. McPhail; Paul N. Varghese; Suzanne S. Kuys (The Scientific World Journal)
Objective. This study investigated cognitive functioning among older adults with physical debility not attributable to an acute injury or neurological condition who were receiving subacute inpatient physical rehabilitation. Design. A cohort investigation with assessments at admission and discharge. Setting. Three geriatric rehabilitation hospital wards. Participants. Consecutive rehabilitation admissions (n=814) following acute hospitalization (study criteria excluded orthopaedic, neurological, or amputation admissions). Intervention. Usual rehabilitation care. Measurements. The Functional Independence Measure (FIM) Cognitive and Motor items. Results. A total of 704 (86.5%) participants (mean age = 76.5 years) completed both assessments. Significant improvement in FIM Cognitive items (Z-score range 3.93–8.74, all P<0.001) and FIM Cognitive total score (Z-score = 9.12, P<0.001) occurred, in addition to improvement in FIM Motor performance. A moderate positive correlation existed between change in Motor and Cognitive scores (Spearman’s rho = 0.41). Generalized linear modelling indicated that better cognition at admission (coefficient = 0.398, P<0.001) and younger age (coefficient = −0.280, P<0.001) were predictive of improvement in Motor performance. Younger age (coefficient = −0.049, P<0.001) was predictive of improvement in FIM Cognitive score. Conclusions. Improvement in cognitive functioning was observed in addition to motor function improvement among this population. Causal links cannot be drawn without further research.